2015
DOI: 10.3390/biom5010121
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of PTS-1 Cargo Proteins by Pex5p: Implications for Protein Mistargeting in Primary Hyperoxaluria

Abstract: Peroxisomal biogenesis and function critically depends on the import of cytosolic proteins carrying a PTS1 sequence into this organelle upon interaction with the peroxin Pex5p. Recent structural studies have provided important insights into the molecular recognition of cargo proteins by Pex5p. Peroxisomal import is a key feature in the pathogenesis of primary hyperoxaluria type 1 (PH1), where alanine:glyoxylate aminotransferase (AGT) undergoes mitochondrial mistargeting in about a third of patients. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(79 reference statements)
2
10
0
Order By: Relevance
“…Following this view, the peroxisomal import machinery does not seem to show a preference based on the AGT quaternary structure, in line with previous reports [ 63 ]. From a structural-thermodynamic point of view, this agrees with the finding that the principal and ancillary targeting sequences of AGT are not part of the monomer–monomer interface [ 54 , 56 ], thus, indicating that there is no obvious competition between Pex5p binding and AGT oligomerization. Previous studies have focused on the equilibrium of the process, i.e., on the ability of Pex5p to recognize monomeric or oligomerized cargoes, as well as on the role of Pex5p binding in counteracting oligomerization, and contrasting results have been reported.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Following this view, the peroxisomal import machinery does not seem to show a preference based on the AGT quaternary structure, in line with previous reports [ 63 ]. From a structural-thermodynamic point of view, this agrees with the finding that the principal and ancillary targeting sequences of AGT are not part of the monomer–monomer interface [ 54 , 56 ], thus, indicating that there is no obvious competition between Pex5p binding and AGT oligomerization. Previous studies have focused on the equilibrium of the process, i.e., on the ability of Pex5p to recognize monomeric or oligomerized cargoes, as well as on the role of Pex5p binding in counteracting oligomerization, and contrasting results have been reported.…”
Section: Discussionsupporting
confidence: 87%
“…AGT folds in the cell cytosol and is then targeted to peroxisomes by a C-terminal PTS1 KKL sequence [ 54 ]. AGT contains one of the weakest PTS1 sequences known for human peroxisomal proteins, as already reported and confirmed by our data ( Table S3 ), but it is efficiently imported due to the high protein levels [ 55 , 56 ]. Consequently, any event that may sequester AGT from the cytosolic pool available for interaction with Pex5 could prevent its proper import.…”
Section: Discussionsupporting
confidence: 87%
“…The corresponding PTS1 peptides showed a similar order of binding affinities, but with approximately 10-fold weaker interaction, consistent with the idea that the C-terminus provides the main specificity but that other ancillary regions also contribute to the affinity. They also demonstrated that binding of peptides to PEX5 stabilized the receptor to thermal denaturation and proteolysis with the extent of protection correlating well with the measured binding affinity [ 26 ]. Direct evidence for structural reorganization of the receptor upon binding cargoes has been presented.…”
Section: Molecular Recognition Of the Pts1 By Pex5mentioning
confidence: 95%
“…Mis-targeting of AGT to mitochondria due to mutations that increase mitochondrial targeting propensity and destabilize protein structure gives rise to the disorder primary hyperoxaluria type 1. The binding of variant AGT proteins and terminal octapeptides to the TPR domain of PEX5 was compared using isothermal titration calorimetry (ITC), molecular modelling and protein stability assays [ 26 ]. The authors concluded that a consensus PTS1 sequence increased the binding affinity principally by reducing the enthalpic penalty of binding, probably reflecting optimization of binding interactions through changes in conformation and buried surface area.…”
Section: Molecular Recognition Of the Pts1 By Pex5mentioning
confidence: 99%
“…After uptake, the macromolecules are challenged by the acidic pH of endosomes/lysosomes, the digestive enzymes of lysosomes, and the endosomal membrane. For a peroxisomal protein such as AGT, it should be able to escape endosome/lysosome degradation, be stable in the cytosol and interact with the import receptor PEX5P to be eventually targeted at the peroxisome (Mesa-Torres et al 2015). ERT of lysosomal storage diseases has made use of carbohydrate chain modifications in the therapeutic glycoprotein in order to enhance its recognition by endocytic carbohydrate receptors.…”
Section: Enzyme Replacement Therapy (Ert)mentioning
confidence: 99%